Maternal microbiome during pregnancy and their impact on the canine microbiome in neonates : a review - Zakošek, Maja (Array, 2020)
The long-standing hypothesis that the neonatal microbiome is acquired during and after birth has been challenged by recent studies in humans using advanced molecular technologies, which identified bacteria and bacterial DNA and RNA in amniotic fluid, placenta, and meconium. Similar studies have recently been conducted on canine neonates, giving a description of the gut microbiota of newborn puppies and a comparison of different types of parturition on theirdevelopment. In this review, we summarize the current knowledge of microbiome and microbial alterations in the canine gut, vagina and oral cavity throughout pregnancy, and their effects on the microbiome of the placenta and the meconium in neonatal puppies. We further compare the microbiome knowledge gained in the last decade on human neonates and draw parallels with canine pregnancy and the neonatal microbiome.